2020
DOI: 10.3390/en13195165
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Gel Time and Dielectric Strength of Epoxy Composite According to the Mixing Ratio of Micro-Fillers

Abstract: The dielectric strength and gel time of epoxy composites vary with the mixing ratio of epoxy resin, hardener, additives, filler, etc., and especially the gel time affects the productivity and economics of ultra-high-voltage (UHV) equipment. However, previous studies focused only on the dielectric strength of epoxy composites for the reliability of UHV equipment. Therefore, a study considering both the dielectric strength and gel time of the epoxy composite is required. In this paper, the characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Curing in an autoclave is unfeasible [9,23], so the temperature of 100 °C is the most suitable for the consolidation process of the composites using the current resin (AR 260), since this temperature allows more controlled curing and prevents the formation of voids. According to Oh et al [24] reported in their study regarding gel time for epoxy composites, the temperature of 80 ºC was the longest, which contributes to a more efficient curing process.…”
Section: Gel Time Water Absorption and Volatiles Content Of The Prepregsmentioning
confidence: 98%
“…Curing in an autoclave is unfeasible [9,23], so the temperature of 100 °C is the most suitable for the consolidation process of the composites using the current resin (AR 260), since this temperature allows more controlled curing and prevents the formation of voids. According to Oh et al [24] reported in their study regarding gel time for epoxy composites, the temperature of 80 ºC was the longest, which contributes to a more efficient curing process.…”
Section: Gel Time Water Absorption and Volatiles Content Of The Prepregsmentioning
confidence: 98%
“…Several authors studied the effect of graphene, MOFs, and alumina loadings on epoxy and studied the thermal and electrical properties. [16][17][18][19] The addition of fillers like SrTiO 3 , Al_FA_A, Al_TPH_450°C_3h, and GO decreases the thermal stability and also it shows 2 distinct degradation stages. The epoxy/TGPAP particulate nanocomposites show initial mass loss of ∼15% and then the major second degradation occurs at 300°C to 490°C.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors studied the effect of graphene, MOFs, and alumina loadings on epoxy and studied the thermal and electrical properties. 1619…”
Section: Resultsmentioning
confidence: 99%
“…Usually, when the concentration of semiconducting filler reaches a certain level or more, the composite material can reveal obvious nonlinear conductivity, and the nonlinear properties intensify as the filler concentration increases. However, the high content of semiconducting materials will lead to less breakdown strength and mechanical properties, which limits the application of and mechanical properties, which limits the application of nonlinear materials stances of inorganic nano-oxides can capably help the breakdown strength of as SiO2 [4], Al2O3 [5], MgO [6], TiO2 [7], ZrO2 [8], ZnO [9], etc. The agglomeratio occurs when the nanofiller is excessively loaded due to the small size effect o with high surface energy, which declines the performance of nanocomposit present research about nanodielectric is conducted on the interface, i.e., the na tion region between nanoparticles and polymer matrix, and the nanoparticle in matically shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%